Perbedaan Kadar Trigliserida Pada Penderita Diabetes Melitus Tipe 2 Dengan Hipertensi Dan Tanpa Hipertensi Di RSUD Moewardi - Siringoring, Yohana Pandora Ristua, dr. Sumardjo, Sp.PD, dr. Listiana Masyita Dewi, M.Sc (2015)
Background: Hypertension is common in patients with diabetes mellitus. Hypertension also increases the risk of cardiovascular disease in diabetes mellitus. High triglyserides level was a sign of dislipidemia. Diabetes mellitus and hypertension accompined with dislipidemia increased the risk of cardiovascular disease. Objective: This study aimed to know the difference of triglycerides level in diabetes mellitus type 2 with hypertension and non hpertension patients. Methods: This study was an observational analiytic with cross-sectional method using patiens medical record in Moewardi General Hospital in December 2014. Total sample was 100, divided into 2 groups of 50 diabetes mellitus type 2 with hypertension and 50 diabetes mellitus type 2 non hypertension groups. The sample were taken using purposive sampling method, then analyzed using Mann-Whitney test by SPSS 17.0 for windows. Result: The characteristics of diabetes mellitus type 2 in woman (51%) and men (49%) were not much different. The largest proportion of the age range is 56-65 years. Mann-Whitney test result was p=0.001 which means there is significant difference of triglycerides levels between two variables. Conclusion: Triglycerides levels in diabetes mellitus type 2 with hypertension is higher compared with diabetes mellitus type 2 non hypertension respondents